2014
DOI: 10.1016/j.irfa.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

What drives investment bank performance? The role of risk, liquidity and fees prior to and during the crisis

Abstract: This paper examines factors that affect the performance of investment banks in the G7 and Switzerland. In particular, we focus on the role of risk, liquidity and investment banking fees. Panel analysis shows that those variables significantly impact upon performance as derived from stochastic frontier analysis (SFA). Given our sample also comprises the financial crisis, we further test for regimes switches using dynamic panel threshold analysis. Results show different underlying regimes, in particular over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 110 publications
4
20
0
Order By: Relevance
“…This disproportionate evolution between loans and deposits can lead to the deterioration of banks' liquidity. Our findings are in line with Cuong Ly (2015), Marozva (2015), Mamatzakis and Bermpei (2014).…”
Section: Non-interest Income and Risksupporting
confidence: 91%
See 1 more Smart Citation
“…This disproportionate evolution between loans and deposits can lead to the deterioration of banks' liquidity. Our findings are in line with Cuong Ly (2015), Marozva (2015), Mamatzakis and Bermpei (2014).…”
Section: Non-interest Income and Risksupporting
confidence: 91%
“…Consequently, the interest revenues decreased which leads to a decrease in the bank performance. Our results are in line with Cuong Ly (2015), Marozva (2015), Mamatzakis and Bermpei (2014).…”
Section: Diversification and Bank Performancesupporting
confidence: 89%
“…Using a sample of 575 listed and non-listed banks and based on the OLS regression, results indicate that there is no significant association between liquidity and probability of default in the long term. Mamatzakis and Bermpei (2014) examined the main factors that explain the bank performance in the G7 and the Switzerland. The sample is composed of 97 banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang, Jiang, Qu, & Wang, 2013). Some studies found positive impact of profitability on risk (Mamatzakis & Bermpei, 2014;Naceur & Omran, 2011).…”
Section: Profitabilitymentioning
confidence: 99%